2014
DOI: 10.7314/apjcp.2014.15.22.9593
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Promotes Apoptosis of SGC-7901 Gastric Cancer Cells through ROCK/PTEN Mediated Mitochondrial Translocation of Cofilin-1

Abstract: Ursolic acid, extracted from the traditional Chinese medicine bearberry, can induce apoptosis of gastric cancer cells. However, its pro-apoptotic mechanism still needs further investigation. More and more evidence demonstrates that mitochondrial translocation of cofilin-1 appears necessary for the regulation of apoptosis. Here, we report that ursolic acid (UA) potently induces the apoptosis of gastric cancer SGC-7901 cells. Further mechanistic studies revealed that the ROCK1/PTEN signaling pathway plays a crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
(20 reference statements)
0
23
0
Order By: Relevance
“…In addition, the corresponding mechanism of action of cofilin-1 may be associated with the promotion of cyclase-associated protein 1 (25). Furthermore, when cofilin-1 protein translocates into the mitochondria from the cytoplasm, it activates cytochrome c release and activation of the caspase cascade, indirectly inducing cell apoptosis (25). The results of the present study demonstrated that ursolic acid significantly inhibited cofilin-1 protein expression in DU145 cells.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…In addition, the corresponding mechanism of action of cofilin-1 may be associated with the promotion of cyclase-associated protein 1 (25). Furthermore, when cofilin-1 protein translocates into the mitochondria from the cytoplasm, it activates cytochrome c release and activation of the caspase cascade, indirectly inducing cell apoptosis (25). The results of the present study demonstrated that ursolic acid significantly inhibited cofilin-1 protein expression in DU145 cells.…”
Section: Discussionmentioning
confidence: 52%
“…It has been reported that cofilin-1 protein will translocate into the mitochondria from the cytoplasm; subsequently, cytochrome c will be released from mitochondria and combine with Apaf-1 to activate caspase-9, so that the caspase cascade will be activated and lead to apoptosis (19). In addition, the corresponding mechanism of action of cofilin-1 may be associated with the promotion of cyclase-associated protein 1 (25). Furthermore, when cofilin-1 protein translocates into the mitochondria from the cytoplasm, it activates cytochrome c release and activation of the caspase cascade, indirectly inducing cell apoptosis (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations